Assessment of the Pattern of Birth Attendance and Its Determinants in Badarganj Upazila, Bangladesh: A Cross-Sectional Study - Sarkar, Paromita; Hossain, Al Sadmom; Akter, Most. Naznin; Shuvo, Sudipto Das; Sarkar, Md. Fazlul Haque (Universitas Andalas, 2025)
Most obstetric complications occur during delivery and cannot be predicted. Therefore, all deliveries should be done through the utilization of SBAs (skilled birth attendants). The study assesses socio-demographic factors and other antenatal or perinatal determinants related to the pattern of birth attendance in Badarganj Upazila, Bangladesh. During the study period, 640 samples were collected from several villages. Data was collected through face-to-face interviews with a well-structured questionnaire and analyzed using descriptive statistics and multinomial logistic regression. The chi-square test was used to determine the association among selected variables in this study. Mothers were aged between 15-45 years. Approximately, half of the mothers (47.0%) used SBAs in their delivery. Maternal educational status, occupation, monthly income, complications during delivery, and antenatal checkups by SBAs were significant determinants. Mothers who took antenatal advice during antenatal visits by SBAs were 2.017 times more likely to use SBAs for conducting delivery compared to those who did not take any delivery advice. Though the ratio of delivery at home is high through the utilization of skilled birth attendants (SBAs), mothers use trained birth assistants (TBAs) or unskilled birth assistants at an alarming rate. Policymakers can use identified factors to overcome this issue by designing interventions and developing healthcare policies.